2008
DOI: 10.1111/j.1468-2958.2007.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Reopening Russian Conversations: The Discourse Particle -to and the Negotiation of Interpersonal Accountability in Closings

Abstract: The article examines how the goals of maintaining and reaffirming interpersonal relationships are accomplished through the details of talk during closing sections of social encounters. On the basis of Russian language telephone conversations between close familiars, the article explicates ways in which interactions may be reopened and, more specifically, the role of the Russian discourse particle -to on utterances that raise new issues in closing environments. The analysis shows that although many kinds of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 64 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…In human interaction, participants communicate this readiness through the exchange of signals, such as okay, ensuring that potentially unraised topics can be addressed (Bolden, 2008;Schegloff & Sacks, 1973). Then, they progress through several steps including well-wishing or suggesting continuity of the relationship, reminiscing about the encounter, exchanging leave-taking signals such as goodbye and finally, taking leave of each other by hanging up a telephone or walking away (Albert & Kessler, 1976;Bangerter, H. Clark, & Katz, 2004;Broth & Mondada, 2013;H.…”
Section: Entering Into Maintaining and Dissolving Shared Intentionalmentioning
confidence: 99%
“…In human interaction, participants communicate this readiness through the exchange of signals, such as okay, ensuring that potentially unraised topics can be addressed (Bolden, 2008;Schegloff & Sacks, 1973). Then, they progress through several steps including well-wishing or suggesting continuity of the relationship, reminiscing about the encounter, exchanging leave-taking signals such as goodbye and finally, taking leave of each other by hanging up a telephone or walking away (Albert & Kessler, 1976;Bangerter, H. Clark, & Katz, 2004;Broth & Mondada, 2013;H.…”
Section: Entering Into Maintaining and Dissolving Shared Intentionalmentioning
confidence: 99%
“…A period followed by a slash (./) indicates a final pitch fall that is larger than the default one. For more information on transcription conventions, see Bolden (2008). [7] Given the silence at line 4, an argument might be made that Misha's ''why'' (line 3) was designed as a complete turn rather than a preface.…”
Section: Notes [1]mentioning
confidence: 99%
“…[2] This investigation is limited to Russian, but preliminary work suggests that repeat prefacing may operate somewhat similarly in English (and perhaps other languages). [3] Russian transcription conventions are described in Bolden (2008). [4] This software can be accessed at www.praat.org.…”
Section: Notes [1]mentioning
confidence: 99%
“…For a complete review of literature on -to, see Bolden (2005). 5 Additionally, -to-marking may be used to invoke participants' prior conversations (Bolden 2003(Bolden , 2005(Bolden , 2008. 6 This and other similarly marked excerpts are from the audiotape that came with the book by Kitaigorodskaia and Rozanova (1994), but all included segments have been retranscribed.…”
Section: Notesmentioning
confidence: 99%
“…These questions can only be answered when interlocutors' own orientations and understandings of the unfolding interaction are examined, and for that actual recorded talk-in-interaction is needed. My research into this particle's use in casual conversation has suggested that it may be deployed strategically to achieve a variety of interactional ends that go beyond information-processing issues, such as to show the speaker's concern for or interest in the addressee (Bolden 2003(Bolden , 2005(Bolden , 2008 or to propose a particular, interactionally driven, understanding of the relationship between the current utterance and prior talk (Bolden 2005). In this chapter, I focus on the discourse connective function of the particle (i.e.…”
Section: The Russian Discourse Particle -Tomentioning
confidence: 99%